Upaya Mengembalikan Prilaku Keagamaan terhadap Penyimpangan Pemahaman Praktek Keagamaan : Potret Prilaku Mimbar Keagamaan - Suaidi Suaidi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
From a religious perspective, diversity is God's gift and will; If God wills, it is certainly not difficult to make His servants uniform and of one type. But He really wants humanity to be diverse, into tribes and nations, with the aim of life being dynamic, learning from each other, and getting to know each other. So, isn't diversity very beautiful? Grateful for the diversity of the Indonesian nation. Apart from diverse religions and beliefs, within each religion there are also diverse interpretations of religious teachings, especially when it comes to religious practices and rituals. Generally, each interpretation of religious teachings has adherents who admit and believe in the truth of the interpretation they practice. The problem is, why do people divide and claim the truth from each other even though the basis is only from religious interpretations. Mutual claims to truth actually announce untruths. If mutual claims to truth are used as a basis for legitimizing divisions on the basis of religious truth, it is very dangerous in the future life of the nation. Religious moderation is a way that can be used as a link to unite those who are divided due to religious interpretations.